A wake-up call for social epidemiologists studying health inequalities: Response to Dijkstra & Horstman. (June 2022) - Kamphuis, Carlijn B.M.; Oude Groeniger, Joost; Beenackers, Mariëlle A.; Van Lenthe, Frank J.
Abstract: In their paper, published in this journal, Dijkstra & Horstman critically reflect on a selection of social epidemiological articles and examine how low socioeconomic status populations are constructed in these articles. They identify four components which they argue represent the "dominant thought style" of this literature: 1) proliferation, 2) generalization, 3) problematization and 4) individualization. We largely agree with their first two points, but strongly disagree with the other two, and explain why in our reply. All in all, we believe that their analysis is a wake-up call for social epidemiologists, rightly pointing to the risk that the relevance and moral origins of the use and study of categories, like 'low socioeconomic status', can easily become less visible, and therefore should be articulated and explained every time.